A Theoretical Model for RF Propagation within Rectangular Enclosures Using Waveguide Concepts - Rodriguez, Ricardo; G. Lewis, Winston (New Approaches in Engineering Research Vol. 16, 2021)
Adequately identifying and managing hazards at the workplace can be a tedious task which extends into the realm of uncertainty, probability and prediction models in order to fully comprehend the nature of the hazard. As such, organizations cannot be blamed for knowledge gaps in the training of personnel they contract to ensure a safe and healthy work environment, especially where there are latent hazards. Electromagnetic wave propagation at frequencies in the SAR (specific absorption rate) region is a special concern to authorities involved in setting RF (radiofrequency) and microwave exposure guidelines. Despite that there is no conclusive evidence to suggest that non-ionizing electromagnetic radiation causes adverse health effects other than thermal, no effort should be spared to ensure that workers and the public at large are adequately protected from unnecessary exposure to radiation. Standards however set exposure limits for free space, plane wave propagation but fall short in compiling information on intensities of these waves after they undergo reflection and diffraction from wall surfaces. This review visits a theoretical model for potential energy build-up due to RF propagation in confined spaces that are of waveguide design but with larger dimensions. Such confined spaces include silos, tanks, pipes, air-condition ducts, tunnels, and operator rooms on board vessels. In these confined spaces rf waves reflect off of the walls and combine constructively or destructively with incident waves producing reinforcement or cancellation respectively. Where there is reinforcement, the intensity of the wave for a particular distance in accordance with the standard, may exceed the exposure limit for this distance from the source thereby exposing the worker to larger intensities than the accepted limit and presenting a potential health and safety threat. In this way, waveguide theory and physics principles have been proposed as the building blocks for the model construction.